Professional trajectories of women in jazz. A matter of gender, authenticity, and musical specialization. - Muñoz-García, Rebeca (Journal of Gender Studies, 2026)
Artistic professions reflect practices that often render trajectories defined by gender relations invisible. This article analyzes how musical specialization, and the idea of jazz 'authenticity' determine professional opportunities and difficulties from a comparative perspective in Spain and the United States through qualitative interviews with women in the contemporary jazz scene for the first time. The results show that musical specialization is a relevant sociological category. Singers and instrumentalists negotiate their participation and recognition in the scene to the extent that music is an expression of their own bodies and/or their musical capital is challenged because they are women. Moreover, leadership and composition are activities that are challenging to attain not only because they are traditionally perceived as masculine but also because they offer greater professional recognition. However, being a leader or composer may become an inevitable strategy for professional inclusion that allows female musicians to create their own opportunities.